THE IMPACT OF TRAUMA FOR RELIGIOUS IDENTITY AFTER CIVIL CONFLICT: STUDY AT BOARDING SCHOOL BABUL ALA NURILLAH BEUTONG ATEUH NAGAN RAYA ACEH INDONESIA - Jannah, Miftahul; Kamsani, Siti Rozaina; Ariffin, Nurhazlina Mohd (Psikoislamedia: Jurnal Psikologi, 2021)
The impact of prolonged civil conflict in Aceh has caused lost family and mental disorder to the local community. One of the tragedy occurred during conflict in Aceh was the killing tragedy in Boarding School Babul 'Ala Nurillah, Blang Meurandeh village Beutong Blang Galang Nagan Raya Aceh Province Indonesia on July 23, 1999 and killed more than 50 man when they are in Boarding School ( Dayah) and learn Islamic knowledge.The peace agreement after conflict between Free Aceh Movement and Indonesia Goverment has 16 years ago since August 18, 2005. They are saw their husband killed by army, andmany women became widows and became poor life. The purpose of this study is to know how the traumatic post conflict and misdevelopment about the religious identity. The Method of this study used quantitative and qualitative method, used scale TSI (Trauma Syndrome Inventory) for trauma by Briere with 100 items and MRPI (Muslim Religious-Personality Inventory)  for scale religious identity. MRPI has 47 item. The sample in this research 25 Woman and 5 man who directly saw the extrajudicial killing, this sample technique used random assigned sampling.The result showed that the victims there are have traumatized is: high trauma 3, low trauma 3, and middle trauma 24 person . The result of this study is that there is a relationship between trauma and religious identity is low  r = -0,312. The correlation beetween trauma and Islamic worldview and spiritual is r = 0.312 (low), trauma with ritual r= 0.543 (medium), trauma with muamalat = 0.157 (very low). This meaning that although the victims feel traumatized but their ritual (hablun min Allah) still good in medium correlation, but the correlation between trauma and Islamic worldview and spiritual is low, and correlation between trauma and mu’amalat (hablun min an-naas) is very low, as well as in religious personality which is divided into Islamic worldview and spiritual, ritual (hablun minallah) and muamalat (hablun min an-naas). After twenty years ago they can to growth with their self and they want to forgotten the tragedy July 23 1999, and want to live in peace. And now they have the commitment to explore and learn Islamic knowledge again after twenty years ago they life without learning the Islamic knowledge in boarding school.